New synthesis of phenyl-isothiocyanate C-functionalised cyclams. Bioconjugation and 64Cu phenotypic PET imaging studies of multiple myeloma with the te2a derivative. Issue 46 (30th September 2015) - Halime, Zakaria; Frindel, Mathieu; Camus, Nathalie; Orain, Pierre-Yves; Lacombe, Marie; Chérel, Michel; Gestin, Jean-François; Faivre-Chauvet, Alain; Tripier, Raphaël
Abstract : New synthesis of bifunctionalised cyclams and 64 Cu-PET imaging study. Abstract : Azamacrocyclic bifunctional chelating agents (BCAs) are essential for the development of radiopharmaceuticals in nuclear medicine and we wish to prove that their bioconjugation by a function present on a carbon atom of the macrocyclic skeleton is a solution of choice to maintain their in vivo inertness. Based on our very recent methodology using a bisaminal template and selective N -alkylation approach, a new synthesis of conjugable C -functionalised teta, te2a and cb-te2a has been developed. These chelators have indeed a growing interest in nuclear medicine for positron emission tomography (PET) and radioimmunotherapy (RIT) where they show in several cases better complexation properties than dota or dota-like macrocycles, especially with 64 Cu or 67 Cu radioisotopes. Chelators are bearing an isothiocyanate grafting function introduced by C -alkylation to avoid as much as possible a critical decrease of their chelating properties. The synthesis is very efficient and yields the targeted ligands, teta-Ph-NCS, te2a-Ph-NCS and cb-te2a-Ph-NCS without fastidious work-up and could be easily extended to other cyclam based-BCAs. The newly synthetised te2a-Ph-NCS has been conjugated to an anti mCD138 monoclonal antibody (mAb) to evaluate its in vivo behavior and potentiality as BCA and to explore a first attempt of PET-phenotypic imaging in multiple myeloma (MM). Mass spectrometry analysis of the immunoconjugate showed that up to 4 chelates were conjugated per 9E7.4 mAb. The radiolabeling yield and specific activity post-purification of the bioconjugate 9E7.4-CSN-Ph-te2a were 95 ± 2.8% and 188 ± 27 MBq mg −1 respectively and the immunoreactivity of 64 Cu-9E7.4-CSN-Ph-te2a was 81 ± 7%. Animal experiments were carried out on 5T33-Luc(+) tumor bearing mice, either in subcutaneous or orthotopic. To achieve PET imaging, mice were injected with 64 Cu-9E7.4-CNS-Ph-te2a and acquisitions were conducted 2 and 20 h post-injection (PI). A millimetric bone uptake was localised in a sacroiliac of a MM orthotopic tumor. Nonspecific uptakes were observed at 2 h PI but, unlike for the tumor, a significant decrease was observed at 20 h PI which improves the contrast of the images.